Posttraumatic Chondrocyte Apoptosis in the Murine Xiphoid. (October 2013) - Davis, Christopher G.; Eisner, Eric; McGlynn, Margaret; Shelton, John M.; Richardson, James; Borrelli, Joseph; Chen, Christopher C.T.
Objective: To demonstrate posttraumatic chondrocyte apoptosis in the murine xiphoid after a crush-type injury and to ultimately determine the pathway (i.e., intrinsic or extrinsic) by which chondrocytes undergo apoptosis in response to mechanical injury. Design: The xiphoids of adult female wild-type mice were injured with the use of a modified Kelly clamp. Postinjury xiphoid cartilage was analyzed via 3 well-described independent means of assessing apoptosis in chondrocytes: hematoxylin and eosin staining, terminal deoxynucleotidyl transferase dUTP nick end labeling assay, and activated caspase-3 staining. Results: Injured specimens contained many chondrocytes with evidence of apoptosis, which is characterized by cell shrinkage, chromatin condensation, nuclear fragmentation, and the liberation of apoptotic bodies. There was a statistically significant increase in the number of chondrocytes undergoing apoptosis in the injured specimens as compared with the uninjured specimens. Conclusions: Chondrocytes can be stimulated to undergo apoptosis as a result of mechanical injury. These experiments involving predominantly cartilaginous murine xiphoid in vivo establish a baseline for future investigations that employ the genetic and therapeutic modulation of chondrocyte apoptosis in response to mechanical injury.